Validation of Simple Equations Describing the Adsorption of Binary Gas Mixtures onto Surfaces with an Asymmetric Distribution of Adsorption Energy - Paweł Szabelski; Krzysztof Nieszporek; Mateusz Drach (Adsorption Science & Technology)
The Monte Carlo simulation method was used to test the accuracy of approximate equations derived for binary gas adsorption onto a heterogeneous surface characterized by a Dubinin-Astakhov adsorption energy distribution (AED) function. In particular, the Condensation Approximation (CA) was applied to obtain simple equations for the partial adsorption isotherms and phase diagrams in the system for which a separate AED was assumed for each component of the mixture. A few cases involving different relationships between the AEDs associated with the adsorbing components were discussed. Additionally, the results of the proposed theory were compared with exact numerical solutions obtained using the Integral Equation method. From both simulations and numerical calculations, it follows that, in general, the CA is not appropriate for the prediction of binary adsorption equilibria when the individual AEDs are of an entirely different shape. On the other hand, when the AEDs were microscopically correlated, i.e. when the adsorption energy of one component on every site was shifted by a constant value compared to that of the other, the phase diagrams obtained were found to be in a very good agreement with their simulated counterparts.